Molecular markers in plasmodium falciparum linked to resistance to anti-malarial drugs in samples imported from Africa over an eight-year period (2002-2010): impact of the introduction of artemisinin combination therapy - Amor, Aranzazu (BioMed Central, 2012)
BACKGROUND: Drug resistance is a major problem to control Plasmodium falciparum infection in endemic countries. During last decade, African countries have changed first-line treatment to artemisinin-based combinations therapy (ACT); sulphadoxine-pyrimethamine (SP) is recommended for Intermittent Preventive Therapy (IPT). Molecular markers related to P falciparum resistance were analysed for the period of transition from SP to ACT, in isolates imported from Africa. METHODS: A first group of samples was taken in the period between June 2002 and June 2006 (n = 113); a second group in the period between November 2008 and August 2010 (n = 46). Several alleles were analysed by nested PCR-RFLP: 51, 59, 108, 164, in the pfdhfr gene; 436, 437, 540, 581, in the pfdhps gene; 86, 1246, in the pfmdr1 gene and 76, in the pfcrt gene. The prevalence of alleles in the groups was compared with the chi-squared or Fisher's exact tests. RESULTS: The pfdhfr N51I, C59R and S108N were over to 90% in the two groups; all samples had the I164. In the pfdhps, 437 G and 581 G, increased up to 80% and 10.9% (p = 0.024), respectively in the second group. The 540 G decreases (24% to 16.%) and the 436A disappears at the end of the follow-up (p = 0.004) in the second group. The 76I-pfcrt stayed over 95% in the two groups. Prevalence of 86Y-pfmdr1 decreased over eight years. CONCLUSIONS: Pharmacological pressure affects the resistance strains prevalence. As for SP, the disappearance of 436A and the decrease in 540 G suggest that these mutations are not fixed. On the other hand, studies carried out after ACT introduction show there was a selection of strains carrying the SNPs N86Y, D1246Y in pfmdr1. In this work, the prevalence of pfmdr1- D1246Y is increasing, perhaps as a result of selective pressure by ACT. Continued surveillance is essential to monitor the effectiveness of treatments.